Weed ingress in perennial ryegrass (Lolium perenne) and tall fescue (Schedonorus arundinaceus)based swards under dairy grazing - Tozer, K.N.; Minnee, E.M.K.; Greenfield, R.M.; Cameron, C.A. (New Zealand Plant Protection, 2016)
Weed ingress was assessed monthly over four years in a total of six swards of perennial ryegrass (Lolium perenne) or tall fescue (Schedonorus arundinaceus) to which were added a legume (2 species mix) legume and forage herbs (4 species mix) or legumes herbs other grasses (8 species mix) Unsown species (weeds) present were from 13 families of which Asteraceae was the most abundant Asteraceae species increased from